TATA KELOLA PERPUSTAKAAN MENGGUNAKAN BAHASA PEMROGRAMAN VISUAL BASIC 6.0 (Studi Kasus Pada Sekolah Menengah Pertama Negeri 3 Seluma) - Kanedi, Indra; Jauhari, Jauhari; Wulandari, Ayu (Jurnal Media Infotama, 2013)
Utilization of database technology and computer devices saai now very widely used in Indonesia , ranging from large corporations to government organizations have utilized this technology computerized database . Not only because they are easy , but its use also to the flexibility of data , the selection and retrieval is fast and accurate in accordance with the wishes of the user and the administrator . Thousands database no longer needs a pile of paper and a large closet as a place of storage , search specific data no longer needs a long time and effort to membongkat - loading and storage cabinets of documents . Quite an integrated system in a computer that will megerjakannya . Library of SMP N 3 Seluma , is the object of study in which researchers will try mekukan pemutakhirnan library database recording system which is currently under-utilizing the same sekalu tegnologi computer , the study sought to determine how the data -based computer tegnologi can answer the problem on this library